2020
DOI: 10.1186/s12905-020-01120-4
|View full text |Cite
|
Sign up to set email alerts
|

Women’s appraisal, interpretation and help-seeking for possible symptoms of breast and cervical cancer in South Africa: a qualitative study

Abstract: Background In South Africa, breast cancer is the most commonly diagnosed cancer and cervical cancer the leading cause of cancer mortality. Most cancers are diagnosed at a late-stage and following symptomatic presentation. The overall purpose of the study was to inform interventions aimed at improving timely diagnosis of breast and cervical cancer. Methods In-depth interviews were conducted with women with potential breast or cervical cancer symptom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
2
13
0
7
Order By: Relevance
“…( 25) System-level delays are a common occurrence in sub-Saharan Africa which leads to delays in treatment initiation as well as a deterrent for utilizing screening services. (24,25) In comparison to studies in the general population in Africa, we observed high rates of cervical cancer knowledge, which has also been noted in other studies looking at awareness of cervical cancer screening in Botswana. (11,26) Furthermore, women included in our study have undergone treatment for cervical cancer already and likely discussed screening and risk factors in greater detail than women who have not been diagnosed with cancer.…”
Section: Discussionsupporting
confidence: 82%
“…( 25) System-level delays are a common occurrence in sub-Saharan Africa which leads to delays in treatment initiation as well as a deterrent for utilizing screening services. (24,25) In comparison to studies in the general population in Africa, we observed high rates of cervical cancer knowledge, which has also been noted in other studies looking at awareness of cervical cancer screening in Botswana. (11,26) Furthermore, women included in our study have undergone treatment for cervical cancer already and likely discussed screening and risk factors in greater detail than women who have not been diagnosed with cancer.…”
Section: Discussionsupporting
confidence: 82%
“…These women also reported fear or embarrassment of undergoing the screening test itself, and abandonment after a cancer diagnosis. Judgmental attitudes by health care providers have also been reported as a contributing factor to this fear [ 30 ]. System-level delays are a common occurrence in sub-Saharan Africa which leads to delays in treatment initiation and acts as a deterrent for utilizing screening services [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our vignettes were developed to capture aspects of provider symptom interpretation; reasoning, judgements and actions related to investigations and management; referral and feedback processes and consideration of infective or alternative diagnoses. The content of the vignettes was informed by findings from the preceding community-based cross-sectional survey, qualitative IDIs with symptomatic women and from drawing on the literature [ 18 , 20 ]. Briefly, the vignettes described a 50-year-old woman with diabetes mellitus and a breast lump ( scenario 1 ); a 50-year-old woman with diabetes mellitus and breast skin changes ( scenario 2 ); a 35-year-old woman with human immunodeficiency virus (HIV), a vaginal discharge and post coital bleeding ( scenario 3 ) and a 60-year-old woman with post-menopausal vaginal bleeding ( scenario 4 ) ( Appendix A ).…”
Section: Methodsmentioning
confidence: 99%
“…This qualitative sub-study formed part of a larger study aimed at better understanding pathways to care for women with possible breast and cervical cancer symptoms. We used both quantitative and qualitative methods to meet the overall study aim [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%